Preceding cervical cytology in women with high-grade squamous intraepithelial lesion - Songveeratham S. (2014)
Objective: To evaluate the preceding cervical cytology and factors leading to cytohistologic discrepancy in women with high-grade squamous intraepithelial lesion (HSIL) histology. Methods: The records of women who were found to have histologically confirmed HSIL without any associated invasive and glandular lesions, at Chiang Mai University Hospital between January 2005 and May 2009, were reviewed. Cytohistological discrepancy was defined as HSIL histology preceded by low-grade squamous intraepithelial lesion (LSIL) and atypical squamous cells of undetermined significance (ASC-US) smears. Results: The records of 436 HSIL cases were reviewed. The mean age of the women was 45.0 ± 9.3 years. The preceding smear abnormalities were as follows: 275 (63.1%) with HSIL; 50 (11.5%) with atypical squamous cells cannot exclude high-grade squamous intraepithelial lesion (ASC-H); 40 (9.2%) with squamous cell carcinoma; 35 (8.0%) with LSIL; 32 (7.3%) with ASC-US; and 4 (0.9) with glandular abnormality smears. Overall, the rate of cytohistological discrepancy was 15.4% (95% CI 12.1-19.1%). The small size of HSIL and presence of coexisting LSIL are significant independent predictors for cytohistologic discrepancy. Conclusion: Approximately 15% of HSIL cases are under-diagnosed by cytology. Significant factors leading to cytohistologic discrepancy are lesion size and the presence of coexisting LSIL. © 2010 Springer-Verlag.